Implementation of COVID‐19 Preventive Measures and Staff Well‐Being in a Sample of English Schools 2020‐2021. (30th November 2022) - Sundaram, Neisha; Abramsky, Tanya; Oswald, William E; Cook, Sarah; Halliday, Katherine E; Nguipdop‐Djomo, Patrick; Sturgess, Joanna; Ireland, Georgina; Ladhani, Shamez N; Mangtani, Punam; Langan, Sinéad M; Hargreaves, James R; et al.
ABSTRACT: BACKGROUND: We examined fidelity and feasibility of implementation of COVID‐19 preventive measures in schools, and explored associations between adherence to these measures and staff well‐being, to inform policy on sustainable implementation and staff wellbeing. METHODS: Surveys were conducted across 128 schools in England with 107 headteachers and 2698 staff‐members with reference to autumn term 2020, examining school‐level implementation of preventive measures, adherence, and teacher burnout (response rates for headteacher and staff surveys were 84% and 59%, respectively). RESULTS: The median number of measures implemented in primary and secondary schools was 33 (range 23‐41), and 32 (range 22‐40), respectively; most measures presented challenges. No differences were found regarding number of measures implemented by school‐level socio‐economic disadvantage. High adherence was reported for staff wearing face‐coverings, staff regularly washing their hands, (secondary only) desks facing forwards, and (primary only) increased cleaning of surfaces and student hand‐washing. Adherence to most measures was reported as higher in primary than secondary schools. Over half of school leaders and 42% (517/1234) of other teaching staff suffered from high emotional exhaustion. Higher teacher‐reported school‐wide adherence with measures was consistently associated with lower burnout for leaders and other teaching staff. CONCLUSIONS: Findings indicate a tremendous effort in implementing preventive measures and an urgent need to support investments in improving teacher wellbeing.